Ferumoxytol for the treatment of iron deficiency and iron-deficiency anemia of pregnancy. (May 2021) - Gerb, Jesse; Strauss, William; Derman, Richard; Short, Vanessa; Mendelson, Ben; Bahrain, Huzefa; Auerbach, Michael
Introduction: A litany of recent evidence supports the morbidity of intra-natal iron-deficiency anemia and its prodrome, iron deficiency. Oral iron administered during second and third trimesters does not get to the developing fetus if the mother is iron deficient. This is especially concerning as the rapidly developing fetal brain is in particular need of iron sufficiency. Intra-natal iron deficiency is associated with autism, schizophrenia and abnormal brain structure. The obstetrical literature reports an unacceptably high incidence of gastrointestinal adverse events with oral iron. The time iron honored standard in the United States for intravenous iron replenishment in gravidas is iron sucrose. While safe and effective, four to seven visits are required to accomplish what newer formulations can achieve with one. Methods: Ferumoxytol is a superparamagnetic iron oxide linked to polyglucose sorbitol carboxymethylether-binding elemental iron tightly allowing administration of complete replacement doses in 15–30 min. Herein, we report the results of 131 consecutive, non-selected, iron-deficient second- and third-trimester pregnant women who received either 510 mg of intravenous (IV) ferumoxytol twice or 1020 mg once. Results: Hemoglobin and iron parameter increments were highly statistically significant. No adverse events were reported. We report how a single infusion is safe and effective as the same dose over two visits, saving an unnecessary visit and IV placement, while reducing cost. Conclusion: Ferumoxytol represents an efficacious and safe method of administration of IV iron which improves convenience for patients and practitioners, and is cost saving due to fewer visits. Plain language summary: One or two infusions of intravenous iron for iron deficiency or iron-deficiency anemia of pregnancy simplifies care This study was conducted to highlight the inconvenience of multiple doses of IV iron and how administering the same dose in one or two infusions simplifies care. We report how a single infusion is as safe and effective as the same dose over two visits, saving an unnecessary visit and IV placement, while reducing cost. This study supports a growing body of evidence, to date, unreported, with ferumoxytol in pregnancy, reporting improved convenience and decreased costs with higher doses of IV iron in one or two visits.